Turkey trouble - Silvano, Wendi, 1962- (Marshall Cavendish, 2009)
As Thanksgiving Day approaches, Turkey nervously makes a series of costumes, disguising himself as other farm animals in hopes that he can avoid being served as Thanksgiving dinner.